Peningkatan Kompetensi Guru-Guru IPA dalam Mengimplementasikan Strategi Pembelajaran Penyelesaian Masalah - Muhiddin Palennari; Firdaus Daud; Saparuddin Saparuddin (DEDIKASI, 2020)
The purpose of this community service is to improve the competence of science teachers in implementing problem solving strategies. This activity is carried out according to the standard of the learning process which states that learning can be carried out by scientific methods, inquiry, problem-based learning and project-based learning in all subjects. The learning process has been carried out by teachers in Takalar Regency but it still needs to be improved in its implementation. The teachers who are targeted in this service are science teachers in Takalar Regency who are members of the MGMP IPA forum. One of the routine activities that are always carried out by the MGMP is training to improve professional competence and pedagogical competence. The form of this service activity is the delivery of subject matter with lecture methods and questions and answers then carried out the process of preparing the problem solving learning then carried out the process of preparing the problem solving learning package. The product of this activity is the packaging of problem-solving learning tools that will be implemented in the classroom.